Uzdasi u poodmakloj dobi - Bujić, Bojan (Muzikološki zbornik, 2007)
Petrarch's sonnet "Se la mia vita da l'aspro tormento", in which the poet is expressing the hope that advanced age will bring him the courage to admit to his lady his long suppressed feelings, is conceived as a single sentence. The three sixteenth-century composers whose settings are discussed - Pietro Vinci, Giaches de Wert and Luca Marenzio, approach their tasks differently. Vinci employs a reserved, motet-influenced style, Wert delights in responding to Petrarch's suggestion of the waning beauty and advancing years with an ingenious symbolic scheme of cadential points, while Marenzio, reacting to the current fashion, opts for a texture in which singable phrases are shared by all four voices. In so doing, Marenzio slows down the pace of delivery and does not quite come up to the intensity with which Wert manages to rise to the challenges offered by Petrarch.
Keywords: glasba; kadenčne sheme; madrigal; music; Petrarca, Francesco, 1304-1374; retorika; rhetoric; vodenje glasov